The dynamics of informal support and social service delivery systems in Langa, Guguletu and Khayelitsha - Nghatsane, David D. M (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1992.